Tratamento físico e químico de efluente de laticínios com o uso de coagulantes orgânicos - Fraisoli, Dioni (2019)
Failure to treat the effluent generated by the dairy industry can lead to environmental and human health problems. Environmentally correct alternatives are being studied to the detriment of the use of chemical coagulants. The present work had the objective of using organic coagulants Tanino and Moringa Oleífera in the processes of coagulation / flocculation / sedimentation / filtration in order to compare them in relation to the efficiency in the processes. Different dosages and pH variations were applied to the coagulants by means of Jar-Test tests. It was evaluated the efficiency in the removal of the parameters apparent color, turbidity, conductivity, total dissolved solids, pH after the coagulation / flocculation / sedimentation processes and the same parameters plus chemical oxygen demand (COD) after the filtration process in order of comparing them and also to verify if after the treatments the analyzed values are within the limit established by the legislation. The coagulant Tanino proved to be more efficient for the treatments. It obtained maximum removals of apparent color and turbidity after the Jar-Test tests of 89.81% and 87.32% respectively. After filtration, it obtained maximum removals of 99% for color, 99.52% for turbidity and 95.39% for COD. For the Moringa Oleifera coagulant, after Jar-test assay obtained maximum removal in the values of 50.52% for apparent color and 43, 25% for turbidity. After the filtration obtained the highest percentages of removal of apparent color, turbidity and COD of 96.63%, 97.89% and 93.7%. For the analysis of the parameters electrical conductivity and pH, there were no significant changes during the treatments and an increase in the analysis of total solids dissolved for both processes was observed. There were no significant variations for any parameter in relation to the concentration of coagulants and acid pH was the most suitable for the tests. Greater efficiency was shown for the processes together. After filtration all parameters met the relevant legislation with the exception of COD.